PENDIDIKAN ANAK DALAM TRILOGI KEILMUAN PENDIDIKAN AGAMA ISLAM - Asmawi, Muhammad Nur (Musawa: Journal for Gender Studies, 2019)
Religion (Islam) and education are two things which are interrelated. Through religion, humans are formed into whole people in accordance with the values of Islamic teachings. The development process is through education because through education, children will become more mature and more capable both in terms of intelligence and mental attitude. Religion is intended to form a complete human being by directing children to become people of faith and piety. The implementation of scientific trilogy of Islamic Religious Education is described in five aspects of Islamic Religious education, namely: aspects of the Koran-Hadith, aspects of aqidah/faith, aspects of morals, aspects of fiqhi/worship, and aspects of history/history of Islamic civilization. Aqeedah material emphasizes the formation of the belief that God is the origin and purpose of human life. Moral material is directed to prepare students to have Islamic morals and ethics as a whole person of Muslims and put into practice in their daily lives.